A country of cities : a manifesto for an urban America - Chakrabarti, Vishaan (Metropolis Books, 2013)
Argues that well-designed cities are the key to solving the United States great national challenges: environmental degradation, unsustainable consumption, economic stagnation, rising public health costs and decreased social mobility.